Work-Life Balance Strategies and Employees’ Engagement in the Food and Beverage Industry in Rivers State - B. M. Nwibere (European Science Publishing, 2023)
This study explores the nexus between work-life balance (WLB) strategies and employees’ engagement (EE) within the food and beverage (F&B) industry. Employing a quasi-experimental design, data was gathered from 165 employees across selected F&B organizations using a closed-ended Likert-type scale questionnaire. Data analysis via Pearson’s Product Moment correlation (PPMC) statistical technique revealed a positive and significant relationship between the dimensions of work-life balance (WLB) strategies and measures of employees’ engagement (EE) within the food and beverage (F&B) industry. Specifically, the results indicate a robust positive and significant correlation between Work interference with personal life (WIPL) and the measures of employees’ engagement: employees’ emotional engagement (EEE) and employees’ behavioral engagement (EBE), with values ranging from 0.894 to 0.881 respectively. Additionally, personal life interference with work (PLIW) demonstrates a notable positive correlation with the measures of employees’ engagement, attributing to 72.5% to 83.5% of emotional and behavioral engagement, respectively. Furthermore, work enhancement of personal life (WEPL) initiatives and personal life enhancement of work (PLEW) initiatives exhibited very strong positive associations with the measures of employees’ engagement, explaining up to 74% to 85% of emotional and behavioral engagement, respectively. These findings corroborate prior research, highlighting the significance of addressing Work-Life Balance issues to bolster employees’ engagement levels. Practically, the study underscores the importance for managers in the Food and Beverage to prioritize strategies that mitigate work-life interference, such as flexible scheduling and family-friendly policies, to foster higher EE levels. Tailored initiatives and training programs should be implemented to address specific WLB aspects identified within organizations, while fostering open communication channels to identify areas for improvement. By prioritizing WLB and supporting employee well-being, managers can cultivate a more engaged and productive workforce, ultimately contributing to organizational success. Other theoretical and practical implications for promoting WLB and fostering employees’ engagement in the Nigerian workplace are also discussed.
Keywords: Work-life Balance Strategies, Employees’ Engagement, Emotional Engagement, Behavioral Engagement, Work Interference with Personal-Life, Personal-Life Interference with Work, Personal Life Enhancement Of Work, Work Enhancement Of Personal-Life.